Prospects for the Application of Brick Walls in Modern Housing Construction Under Construction in Uzbekistan.: Potensi Penerapan Dinding Bata dalam Konstruksi Perumahan Modern di Uzbekistan - Xakimovna, Xaydarova Kamola; Maxmudovna , Ismatova Dilfuza (Indonesian Journal of Law and Economics Review, 2024)
Since gaining independence, the Republic of Uzbekistan has undertaken extensive reforms across its national economy, emphasizing the incorporation of new technologies, scientific advancements, and best practices. This article focuses on the construction industry, a key sector in the nation's development. A primary objective is the promotion of energy-efficient construction methods for buildings and structures. The study employs a multifaceted approach, integrating modern technologies and drawing from global experiences. The results emphasize the ongoing development and progress in the construction sector, showcasing a commitment to sustainability and innovation. The implications of this research extend beyond national borders, contributing valuable insights to the global discourse on energy-efficient construction practices. Highlights: National Economic Reforms: The article explores the impact of independence on Uzbekistan's economy, focusing on comprehensive reforms in various sectors. Energy-Efficient Construction: A central theme involves the urgent need for energy-efficient practices in the construction industry, aligning with global sustainability goals. Technological Advancements: The content highlights the incorporation of new technologies and scientific achievements as crucial drivers of progress in the construction sector. Keywords: Independence, Uzbekistan, Energy-efficient construction, Reforms, Sustainable development.